Incomplete atrioventricular dissociation and isorhythmic atrioventricular dissociation during general anesthesia with desflurane and remifentanil: A case report. Issue 1 (7th June 2017) - Hirase, Masayasu; Seto, Mika; Koga, Sayo; Takaoka, Masao; Kita, Ryosuke; Kikuta, Toshihiro
Abstract: We encountered a patient who experienced incomplete atrioventricular (A‐V) dissociation and isorhythmic A‐V dissociation during general anesthesia with desflurane and remifentanil. A 38‐year‐old man was scheduled to undergo extraction of both the upper and the right lower impacted wisdom teeth under general anesthesia. After anesthesia induction, we maintained anesthesia with desflurane and remifentanil. After 15min, incomplete A‐V dissociation was observed on electrocardiography (ECG). After atropine sulfate 0.3mg was administered intravenously, isorhythmic A‐V dissociation was observed. Atropine sulfate 0.2mg was administered intravenously, and we observed normal ECG findings. Subsequently, no abnormal ECG findings were observed.